CORRELATION BETWEEN MOTIVATION AND STUDENTS ACHIEVEMENT IN MIDWIFERY CARE AND DELIVERY PROGRAM IN AISYIYAH UNIVERSITY YOGYAKARTA - Yulastini, Fitria; Dewi, Novita Puspita; Handayani, Dwi; Petricka, Gracea (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Universitas Aisyiyah Yogyakarta is one of the universities that has implemented Competence Based Curriculum (CBC) system. One of the courses that used CBC system is Midwifery Care in Delivery course, which relates directly to the main job of a midwife. However, there are many students who only obtained C (Unsatisfactory) grade, and they need to retake the course meet the standard grade as determined by Universitas Aisyiyah Yogyakarta. One of the factors influencing study achievement is motivation. Aims: to analyze the relation between study motivation of fourth semester students (academic year 2012/2013) of DIII Midwifery Program, Universitas Aisyiyah Yogyakarta and their achievement in Midwifery Care in Delivery course. Method: This was a quantitative study with analytical survey method and cross sectional approach.Study population was all 223 fourth semester students (academic year 2012/2013) of DIII Midwifery Program, Universitas Aisyiyah Yogyakarta. 143 of them were selected as study subjects. Data was analyzed using Spearmanâs Rank Correlation. Results: The majority of fourth semester students of DIII Midwifery Program had medium motivation in Midwifery Care in Delivery course, with the number reached 96 students (67.1%).Most of fourth semester students of DIII Midwifery Program obtained C (Unsatisfactory) grade in Midwifery Care in Delivery course, with the number reached 67 students (46.9%).There was a significant relation between fourth semester students of DIII Midwifery Program motivation and their achievement in Midwifery Care in Delivery course, where the result of Spearmanâs Rank Correlation test shows the value of correlation coefficient = 0.723 and p value (0.000) (0.05). Conclusion: There was a relation between learning motivation and their achievement in midwifery care in delivery course with a strong degree of correlation. However, further research is expected to discuss all factors that affect the learning achievement such as environment, interests, talents, intelligence, health, learning way, and other variables that can affect.Â